Colômbia, Brasil e Venezuela e os impactos no mercado de trabalho - GARCIA, MARIANA HANSEN; CALVETE, CÁSSIO DA SILVA (Estudos Avançados, 2015)
In the early 21st century, there was a general improvement of the labor market indicators in Latin America compared to the 1990s. In this paper, we intend to examine to what extent it is possible to associate these improved results with the maintenance or reorientation of economic policy. Toward this end, we chose three countries - Venezuela, Brazil and Colombia - that, in our view, have put into place different economic development strategies in the beginning of the new century.